The effects of autologous fecal microbiota transplantation on fear memory and anxiety abnormalities induced by single prolonged stress – Implication of gut-brain axis regulation - Yu-Yen Cheng; Chen-Cheng Lin; Che-Se Tung; Cheng-Che Liu; Yia-Ping Liu (Brain Research Bulletin)
Increasing evidence suggests that alterations in the gut microbiota play a crucial role in the pathophysiology of psychiatric disorders, including post-traumatic stress disorder (PTSD). This implies that restoring gut microbiota might serve as a therapeutic strategy, with autologous fecal microbiota transplantation (FMT) being the most promising treatment due to its effectiveness and fewer pharmacological side effects. However, the hypothesis that adjusting gut microbiota may help to restore the impairment of fear memory is still less examined. To evaluate this hypothesis, we employed single prolonged stress (SPS) rat model to examine the impact of autologous FMT on PTSD-related fear memory extinction retention deficits and increased anxiety, and to investigate changes in the levels of gut microbiota, central monoamines, and plasma corticosterone. The correlations between gut microbiota and central serotonin (5-HT) with fear extinction retention deficits and anxiety were analyzed. Note that littermates were used in the gut microbiota analysis to minimize individual differences. Our results demonstrated that autologous FMT significantly ameliorated SPS-induced deficits in fear extinction retention and conditioned anxiety but did not mitigate unconditioned anxiety. These improvements were significantly correlated with the restoration of 5-HT levels in the medial prefrontal cortex (mPFC), dorsal hippocampus (dHPC), and hypothalamus (HT). Autologous FMT also reversed SPS-induced reductions in plasma corticosterone level. Additionally, fecal microbiota analysis revealed significant changes at the genus level, with the relative abundance of the Prevotellaceae Ga6A1 group reduced after SPS, and Intestinimonas increased by FMT, as well as some taxa significantly correlated with fear extinction retention deficits. This study suggests that autologous FMT offers potential as a novel therapeutic strategy for PTSD.